POLA PENGEMBANGAN DAN EVALUASI KURIKULUM PENDIDIKAN AGAMA ISLAM - H.M. Nasron HK (Universitas Islam Negeri Fatmawati Sukarno, 2015)
The problem discussed in this paper is how the Islamic education curriculum development in schools using the curriculum framework development disciplines. Systematically, this paper discusses the significance of PAI curriculum, curriculum components, approach to curriculum development, curriculum development base, steps in curriculum organization, curriculum organization, competency-based curriculum. The authors assume that Islamic religious education (PAI) as the subjects need to be developed to respond to the demands and dynamics of the community